Electroanatomic mapping reconstruction with photogrammetry across different mapping systems - Talevi, Giacomo; Pannone, Luigi; Della Rocca, Domenico Giovanni; Sorgente, Antonio; Kronenberger, Rani; Overeinder, Ingrid; Bala, Gezim; Almorad, Alexandre; Ströker, Erwin; Sieira, Juan; La Meir, Mark; Sarkozy, Andrea; et al. (Frontiers in Imaging, 2025)
BackgroundAutomatic digital photogrammetry produces digital reproductions of objects using photographs. The aim of this study is to analyze feasibility of photogrammetry for electroanatomic map (EAM) reconstruction from different mapping systems. Furthermore, the possibility to import the reconstructed EAMs in a common working space is evaluated.MethodsAll consecutive patients undergoing EAM with one of the following EAM systems were screened for the study: (1) CARTO™; (2) Ensite™ X; (3) Rhythmia™; (4) Affera™ PRISM-3. All patient geometries were reconstructed from a video acquisition within the source EAM software. The video obtained was processed with Zephyr software and a dense point cloud was obtained. An image or sequence of images was selected to build a 3D mesh. At the end, the mesh was imported in the 3D graphics software Blender.ResultA total of 24 EAMs from 24 patients were included in the study. All EAMs were reconstructed with success using photogrammetry from all 4 mapping systems assessed. The process time was ≈ 25 min. In particular, EAMs were as follows: left atrium (2 Carto; 2 Ensite; 5 Rhythmia; 2 Affera), right atrium (1 Carto; 6 Ensite; 3 Affera) and left ventricles (1 Carto; 2 Ensite). All the reconstructed EAMs were imported in Blender with success. They could be visualized in Blender and all the operations were allowed including moving EAMs in a common working space and EAMs overlap.ConclusionThis study demonstrated for the first time the possibility of realizing 3-D objects from digital video formats of different EAMs.